INPP4B is highly expressed in prostate intermediate cells and its loss of expression in prostate carcinoma predicts for recurrence and poor long term survival. Issue 1 (4th October 2014) - Rynkiewicz, Natalie K.; Fedele, Clare G.; Chiam, Karen; Gupta, Ruta; Kench, James G.; Ooms, Lisa M.; McLean, Catriona A.; Giles, Graham G.; Horvath, Lisa G.; Mitchell, Christina A.
Abstract BACKGROUND Phosphoinositide 3‐kinase (PI3K)/Akt pathway is frequently activated in prostate carcinoma due to the loss of tumor suppressor PTEN, which leads to increased Akt activity. Expression of INPP4B, another negative regulator of the PI3K/Akt pathway, is also reduced in prostate carcinoma. However, uncertainty exists regarding the association of INPP4B expression and biochemical and clinical relapse of prostate carcinoma. METHODS INPP4B expression in benign prostate acini was analyzed by co‐immunofluorescence with cytokeratins (CK) 5, 8, 19, androgen receptor (AR), c‐MET, chromogranin A and Ki67. INPP4B expression in prostate carcinoma was analyzed in two independent cohorts (n = 406). The association of INPP4B with biochemical and clinical prostate carcinoma relapse was assessed by Kaplan–Meier and Cox proportional hazards modeling. RESULTS INPP4B was expressed in luminal epithelium within benign ducts, and was highly expressed in CK5+/CK8+/CK19+/AR−/c‐MET+/Ki67− intermediate cells in proliferative inflammatory atrophic acini. Overall, INPP4B expression was reduced in prostate carcinoma compared to benign epithelium. Absent/low INPP4B expression was associated with reduced biochemical relapse‐free survival (P = 0.01) and increased risk of clinical relapse (P = 0.01). Absence of INPP4B expression was an independent predictor of clinical relapse free survival (P = 0.004) when modeled with Gleason score (P = 0.027) and pathologic stage (P = 0.07). CONCLUSIONS INPP4B is highly expressed in intermediate cells within proliferative inflammatory atrophic ducts, and expression is reduced in prostate carcinoma. Absence of INPP4B expression is associated with poor outcome following radical prostatectomy, and represents an independent prognostic marker of prostate carcinoma clinical recurrence. Prostate 75:92–102, 2015. © 2014 Wiley Periodicals, Inc.